Composite particles containing electrode material and electrodes for electrochemical devices containing the same

JP2025505963AActive Publication Date: 2025-03-05LG ENERGY SOLUTION LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024544810
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-14
Filing Date
2023-01-30
Publication Date
2025-03-05
Estimated Expiration
2043-01-30

AI Technical Summary

Benefits of technology

【0020】 本発明による顆粒は、粒子の表面部にバインダー含量が高く、これによって、電極活物質層を形成するために顆粒を集電体に散布した後、カレンダリングなどの平坦化工程が行われるときに、電極活物質層における顆粒の脱離が減少する。そのため、平坦化工程で用いられる設備(例えば、カレンダーロール)の汚染が減少する。また、前記顆粒を用いて電極を製造することで、電極活物質層の厚さ方向においてバインダー分布が均一に示される電極を得ることができる。そのため、電極活物質層と集電体との接着力が優秀であり、電極活物質層の形態安定性が改善される効果を奏する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025505963000001_ABST
    Figure 2025505963000001_ABST
Patent Text Reader

Abstract

The present invention relates to an electrode and an electrochemical device including the same, the electrode including a current collector and an electrode active material layer formed on the current collector, the electrode active material layer including granules, the granules having a higher binder content in a surface portion than in a center portion.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite particle for a dry electrode and an electrode for an electrochemical element including the same. This application claims priority based on Korean Patent Application No. 10-2022-0013754 filed on January 28, 2022 and Korean Patent Application No. 10-2022-0031703 filed on March 14, 2022, and the contents disclosed in the specification and drawings of said application are incorporated herein in their entirety. [Background technology]

[0002] As the use of fossil fuels has increased rapidly, the demand for alternative and clean energy has been increasing, and as part of this, the field in which research is most active is the field of power generation and storage using electrochemistry. Currently, a representative example of an electrochemical element that uses such electrochemical energy is a secondary battery, and the range of its use is expanding. Lithium secondary batteries, which are representative of such secondary batteries, are not only used as an energy source for mobile devices, but are also being used as a power source for electric vehicles and hybrid electric vehicles that can replace vehicles that use fossil fuels such as gasoline vehicles and diesel vehicles, which are one of the main causes of air pollution, and their range of use is expanding as an auxiliary power source for grid-based power generation.

[0003] Such a secondary battery is manufactured through an electrode manufacturing process, an electrode assembly manufacturing process, and a chemical formation process. The electrode manufacturing process generally involves manufacturing an electrode slurry, coating the electrode current collector with the slurry, and drying the electrode. After drying, subsequent processes such as a rolling process, a slitting process, and a winding process are performed. Among these, the electrode slurry manufacturing process is a process of blending components for forming an electrode active material layer in which an electrochemical reaction actually occurs in the electrode. In detail, the electrode slurry is manufactured in the form of a slurry having fluidity by mixing an electrode active material, which is an essential element of an electrode, other additives such as a conductive material and a filler, a binder for binding between powder particles and adhering to the current collector, and a solvent for imparting viscosity and dispersing powder.

[0004] As described above, in a conventional electrode in which a slurry coating method is applied to form an electrode active material layer, the binder material in the electrode cannot be distributed uniformly in the thickness direction of the electrode, but is distributed in a larger amount intensively on the surface of the electrode active material layer, resulting in a problem that the binding strength between the electrode active material layer and the current collector is not sufficiently secured. This is a phenomenon caused by migration of the binder material to the surface layer due to evaporation of the solvent when the slurry is dried.

[0005] In order to solve these problems, it is necessary to develop electrodes for electrochemical devices in which the binder material is uniformly distributed. Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention aims to provide an electrode having a uniform binder distribution in the thickness direction of an electrode active material layer. Another object of the present invention is to provide granular particles including an electrode material having a specific binder distribution, and a dry electrode manufactured using the same. The objects and advantages of the present invention may be realized by the means and combinations thereof as set forth in the claims. [Means for solving the problem]

[0007] According to a first aspect of the present invention, there is provided a granule for an electrode of an electrochemical element, the granule comprising an electrode active material and an electrode binder, the electrode active material being bound by the electrode binder, the content of the electrode binder in a surface portion being greater than the content of the electrode binder in a central portion relative to a total weight of the electrode active material and electrode binder being 100 wt%, the surface portion being a region extending from the surface of the granule to 30% of the radius toward the center of the granule, and the central portion being the portion other than the surface portion.

[0008] According to a second aspect of the present invention, in the first aspect, the surface portion is a region extending from the surface of the granule to 20% of the radius toward the center of the granule.

[0009] According to a third aspect of the present invention, in the first or second aspect, the surface portion is a region extending from the surface of the granule toward the center of the granule to 10% of the radius.

[0010] According to a fourth aspect of the present invention, in any one of the first to third aspects, the granules have an aspect ratio of 0.5 to 1.0.

[0011] According to a fifth aspect of the present invention, in any one of the first to fourth aspects, the granules have an aspect ratio of 0.75 to 1.0.

[0012] According to a sixth aspect of the present invention, in any one of the first to fifth aspects, the particle diameter D of the granules is 50 is 0.1μm to 1,000μm.

[0013] According to a seventh aspect of the present invention, in any one of the first to sixth aspects, the granules include two or more electrode active material materials.

[0014] According to an eighth aspect of the present invention, there is provided an electrode for an electrochemical element, the electrode comprising a current collector and an electrode active material layer located on the current collector, the electrode active material layer including an electrode active material and an electrode binder, and current collected as a layered structure by introducing granules from any one of the first to seventh sides.

[0015] According to a ninth aspect of the present invention, in the eighth aspect, the electrode active material layer has a multi-layer structure in which two or more unit active material layers are stacked.

[0016] According to a tenth aspect of the present invention, in the eighth or ninth aspect, the electrode active material layer has a difference in binder content (wt%) between the upper 100 wt% and the lower 100 wt% based on a point that is 50% from the current collector in the thickness of the electrode active material layer, of 10 wt% or less.

[0017] According to an eleventh aspect of the present invention, in any one of the eighth to tenth aspects, the electrode active material layer has a binder content difference of 10 wt% or less between a region up to 15% of the thickness of the electrode active material layer from the current collector in a direction toward the electrode surface layer and a region up to 15% of the thickness of the electrode active material layer from the surface layer toward the current collector.

[0018] According to a twelfth aspect of the present invention, in any one of the eighth to eleventh aspects, the current collector has a primer layer disposed on at least one surface, the primer layer covers all or at least a part of the surface, and includes a second conductive material and a second binder.

[0019] According to a thirteenth aspect of the present invention, there is provided an electrochemical device comprising a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, the negative electrode being as described in any one of the eighth to twelfth aspects. Effect of the Invention

[0020] The granules according to the present invention have a high binder content at the surface of the particles, and therefore, when a planarization process such as calendaring is performed after the granules are spread on a current collector to form an electrode active material layer, detachment of the granules from the electrode active material layer is reduced. As a result, contamination of equipment (e.g., calendar rolls) used in the planarization process is reduced. In addition, by manufacturing an electrode using the granules, an electrode having a uniform binder distribution in the thickness direction of the electrode active material layer can be obtained. As a result, the adhesive strength between the electrode active material layer and the current collector is excellent, and the shape stability of the electrode active material layer is improved.

[0021] The following drawings attached to this specification illustrate preferred embodiments of the present invention and, together with the detailed description of the invention, serve to further understand the technical ideas of the present invention. The present invention should not be interpreted as being limited only to the matters described in the drawings. [Brief description of the drawings]

[0022] [Figure 1]1 is a SEM image of granular particles observed in this example. [Diagram 2] 1 shows a cross section of an electrode manufactured by a manufacturing method according to Example 1 of the present invention. [Diagram 3] 4 is a graph showing a binder content distribution in a thickness direction of an electrode active material layer in an electrode prepared by a method according to Example 1 of the present invention. [Figure 4] 1 shows a cross section of an electrode manufactured by a manufacturing method according to Comparative Example 4 of the present invention. [Diagram 5] 13 is a graph showing a binder content distribution in a thickness direction of an electrode active material layer in an electrode prepared by a method according to Comparative Example 4 of the present invention. [Figure 6] 1 is a schematic diagram of an electrode according to an embodiment of the present invention. [Figure 7] FIG. 1 is a schematic diagram of calculating the QBR value of an electrode layer. [Figure 8] 1 is a cross-sectional image of the granular particles produced in Example 1. [Figure 9] 1 is a cross-sectional image of the granular particles produced in Example 2. [Figure 10] 1 is a cross-sectional image of the granular particles produced in Example 3. [Figure 11] 1 is a cross-sectional image of granular particles produced in Comparative Example 1. [Figure 12] 1 is a cross-sectional image of granular particles produced in Comparative Example 2. [Figure 13a] 1 is a graph showing the binder resin content from the center to the surface of granular particles obtained from Examples 1, 2, and 3 and Comparative Examples 1 and 2. [Figure 13b] 1 is a graph showing the binder resin content from the center to the surface of granular particles obtained from Examples 1, 2, and 3 and Comparative Examples 1 and 2. [Figure 14] 4 shows the distribution of electrode load of the negative electrode according to Example 1. [Figure 15] 1 shows the distribution of the electrode load amount of the negative electrode according to Comparative Example 1. [Figure 16]1 is a photograph showing granules immobilized within a cured epoxy resin. [Figure 17] 1 is a schematic diagram showing a granular particle of the present invention, with the surface portion and the center portion being divided into parts; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] The present invention will be described in detail below. However, the present invention is not limited to the following content, and each component may be modified in various ways or mixed selectively as necessary. Therefore, it should be understood that all modifications, equivalents, or alternatives included in the spirit and technical scope of the present invention are incorporated.

[0024] Throughout the specification, when a part "comprises" a certain element, it does not mean excluding other elements, but means that the part may further include other elements, unless otherwise specified.

[0025] The terms "about," "substantially," and the like, used throughout this specification, when given the meaning given, are used to mean a numerical value or a approximation thereof, given the inherent manufacturing and material tolerances, and are used to prevent unconscionable infringers from unfairly using disclosures in which precise or absolute numerical values ​​are recited to aid in the understanding of this application.

[0026] Throughout this specification, the phrase "A and / or B" means "A or B, or all of these."

[0027] Certain terminology used herein is for convenience and is not limiting. Terms such as "top," "bottom," "left," "right," "front," "rear," "inside," and "outside" are used to describe relative positions and orientations of components relative to one another, rather than absolute positions, or may indicate positions and orientations in the drawings to which reference is made. The above terms include other words containing these terms, derivatives thereof, and words of similar meaning.

[0028] As used herein, the "glass transition temperature, Tg," may be measured by conventional methods known in the art, for example, by differential scanning calorimetry (DSC).

[0029] In the present specification, the term "porosity" refers to the ratio of the volume of pores to the total volume of a structure, and may be used interchangeably with terms such as porosity and porosity, with the unit being %. In the present invention, the measurement of the porosity is not particularly limited, and in one embodiment of the present invention, for example, the measurement may be performed by a BET (Brunauer-Emmett-Teller) measurement method using nitrogen gas or a mercury penetration method (Hg porosimeter) and ASTM D-2873. Alternatively, the true density of the separator may be calculated from the density (apparent density) of the separator, the composition ratio of the materials contained in the separator, and the density of each component, and the porosity of the separator may be calculated from the difference between the apparent density and the true density (net density).

[0030] The term "average particle size D50" used in the specification means the particle size at 50% of the cumulative particle number distribution by particle size, and the particle size may be measured using a laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500), and the particle size distribution is calculated by measuring the diffraction pattern difference according to particle size when the particles pass through a laser beam. The D50 particle size can be measured by calculating the particle diameter at the 50% point of the cumulative particle number distribution by particle size in the measuring device.

[0031] In this specification, the "thickness" of each layer included in the electrode may refer to a value measured by a known method for measuring thickness. The method for measuring thickness is not limited thereto, but may be, for example, a value measured using a thickness gauge (Mitutoyo, VL-50S-B).

[0032] The "specific surface area" used in the present specification may be a value measured by a known method for measuring a specific surface area. The method for measuring the specific surface area is not limited thereto, and may be, for example, a value measured by a flow method or a stationary method.

[0033] The present invention relates to granules for electrodes and electrodes for electrochemical devices formed by accumulating the granules in a layered structure under pressure. The electrochemical device of the present invention includes all devices that perform electrochemical reactions, and specifically includes all types of primary batteries, secondary batteries, fuel cells, solar cells, and capacitors such as supercapacitors. In the present invention, the electrochemical device is preferably a secondary battery, and more preferably a lithium ion secondary battery.

[0034] <Granules> The electrode granule of the present invention will be described in detail below. In the present invention, the granule may have the form of a composite particle containing an electrode active material, an electrode binder, and any optional component added as required. In one embodiment of the present invention, the granule may be a secondary particle formed by binding two or more electrode active material particles with the electrode binder and granulating them. In the present invention, the electrode active material may mean a particle aggregate. Here, the diameter of each particle of the electrode active material may be 0.05 μm to 2 μm. In one embodiment of the present invention, the electrode active material may be 80 wt% or more or 90 wt% or more of the total weight of the granule, and the electrode binder may be contained in an amount of 20 wt% or less or 10 wt% or less. In one embodiment of the present invention, the granule may further contain an electrode conductive material as an optional component as required. The electrode conductive material may be contained in a range of 0.1 wt% to 20 wt%, preferably 0.1 wt% to 10 wt%, with respect to 100 wt% of the granule. For example, the conductive material may be contained in the granules in a range of about 0.1 wt % to 5 wt %.

[0035] According to one embodiment of the present invention, the content of the electrode active material in the granules may be 85wt% to 98wt%. Within this range, the content of the electrode binder may be 0.5wt% to 10wt%, and the content of the electrode conductive material may be 0.5wt% to 5wt%. According to yet another embodiment, the content of the electrode active material may be 90wt% to 98wt%, the content of the electrode binder may be 0.5wt% to 5wt%, and the content of the electrode conductive material may be 0.5wt% to 5wt%.

[0036] 17 is a diagram showing the surface and center portions of a granule of the present invention. Referring to this diagram, in the present invention, the granule has a greater amount of electrode binder contained in the surface portion 102 of the granule than in the center portion 101 of the granule. The amount of binder may refer to weight or volume.

[0037] In addition, or independently, the granule may have a content (wt%) B of the electrode binder contained in the center 101 of the granule relative to the total weight of the granule (100 wt%). c / G t The content (wt%) of the electrode binder contained in the surface portion 102 of the granule B s / G t Here, the B c is the weight of the binder contained in the core, and B s is the weight of the binder contained in the surface area, and G t means the total weight of the granular particles.

[0038] In addition, or independently, the granule may have a content (vol%) B of the electrode binder contained in the center 101 of the granule relative to the total volume 100 vol% of the granule. c / G t The content of the electrode binder contained in the surface portion 102 of the granule is vol% B s / G t Here, the B c is the volume of the binder contained in the core, and B s is the volume of the binder contained in the surface area, and G tmeans the total volume of the granular particles.

[0039] Here, the surface portion may mean a region near the surface of the granule from the surface of the granule to a predetermined depth toward the center of the granule. The central portion means a portion other than the surface portion. In one embodiment of the present invention, the surface portion may mean, more specifically, a surface region from the surface of the granule toward the inside, specifically, up to 30% of the radius toward the center of the granule. In one embodiment of the present invention, the surface portion may mean a surface region from the surface of the granule to 30% of the radius, up to 20% of the radius, up to 15% of the radius, up to 10% of the radius, or up to 5% of the radius. Desirably, the surface portion may mean a surface region from the surface of the granule to 20% of the radius.

[0040] On the other hand, in one embodiment of the present invention, the surface portion may refer to a region from the center of the granule to the outside of the granule, covering 70% or more of the ranule surface in the radius. In one embodiment of the present invention, the surface portion may refer to a region covering 80% or more, 85% or more, 90% or more, or 95% or more of the granule surface in the radius.

[0041] In one embodiment of the present invention, the center of the granule may refer to a point that is 1 / 2 the maximum diameter of the granule. In the present invention, the radius may refer to a distance from the center of the granule to each point on the granule surface. In one embodiment of the present invention, the surface portion and the center portion may be divided based on points that are the same distance from each surface of the granule along each radius, specifically, points up to 30%, up to 20%, up to 10%, up to 5%, or up to 1% of the radius from the surface.

[0042] In one embodiment of the present invention, in a region from the center of the granule to the surface of the granule at a radius of 90% or more, the content of the electrode binder relative to the total weight of the granule in that region (100 wt%) may be 50 wt% or more, 60 wt% or more, 70 wt% or more, 80 wt% or more, or 90 wt% or more.

[0043] In yet another embodiment of the present invention, in a region from the center of the granule to the surface of the granule at a radius of 95% or more, the content of the electrode binder relative to the total weight of the granule in that region (100 wt%) may be 50 wt% or more, 60 wt% or more, 70 wt% or more, 80 wt% or more, or 90 wt% or more.

[0044] In yet another embodiment of the present invention, in a region from the center of the granule to a radius of 99% or more of the surface of the granule, the content of the electrode binder relative to the total weight of the granule in that region (100 wt%) may be 50 wt% or more, 60 wt% or more, 70 wt% or more, 80 wt% or more, or 90 wt% or more.

[0045] In one embodiment of the present invention, in a region from the center of the granule to the surface of the granule at a radius of 90% or more, the content of the electrode binder relative to 100 vol% of the total volume of the granule in that region may be 50 vol% or more, 60 vol% or more, 70 vol% or more, 80 vol% or more, or 90 vol% or more.

[0046] In yet another embodiment of the present invention, in a region from the center of the granule to a radius of 95% or more of the surface of the granule, the content of the electrode binder relative to 100 vol% of the total volume of the granule in that region may be 50 vol% or more, 60 vol% or more, 70 vol% or more, 80 vol% or more, or 90 vol% or more.

[0047] In yet another embodiment of the present invention, in a region from the center of the granule to the surface of the granule at a radius of 99% or more, the content of the electrode binder relative to 100 vol% of the total volume of the granule in that region may be 50 vol% or more, 60 vol% or more, 70 vol% or more, 80 vol% or more, or 90 vol% or more.

[0048] In one embodiment of the present invention, in a granule surface region within a radius of 10% from the granule surface, the content of the electrode binder relative to the total weight of the granule in that region (100 wt%) may be 50 wt% or more, 60 wt% or more, 70 wt% or more, 80 wt% or more, or 90 wt% or more.

[0049] In yet another embodiment of the present invention, in a region from the surface of a granule to a radius of 5% of the surface of the granule, the content of the electrode binder relative to the total weight of the granule in that region (100 wt%) may be 50 wt% or more, 60 wt% or more, 70 wt% or more, 80 wt% or more, or 90 wt% or more.

[0050] In yet another embodiment of the present invention, in a region from the granule surface to the granule surface at a radius of 1% or more, the content of the electrode binder relative to the total weight of the granule in that region (100 wt%) may be 50 wt% or more, 60 wt% or more, 70 wt% or more, 80 wt% or more, or 90 wt% or more.

[0051] In one embodiment of the present invention, in a granule surface region within a radius of 10% from the granule surface, the content of the electrode binder relative to the total volume of the granule in that region (100 vol%) may be 50 vol% or more, 60 vol% or more, 70 vol% or more, 80 vol% or more, or 90 vol% or more.

[0052] In yet another embodiment of the present invention, in a granule surface region from the granule surface to 5% of the radius, the content of the electrode binder relative to 100 vol% of the total volume of the granule in that region may be 50 vol% or more, 60 vol% or more, 70 vol% or more, 80 wt% or more, or 90 vol% or more.

[0053] In yet another embodiment of the present invention, in a region from the surface of a granule to a radius of 1% or more of the surface of the granule, the content of the electrode binder relative to 100 vol% of the total volume of the granule in that region may be 50 vol% or more, 60 vol% or more, 70 vol% or more, 80 vol% or more, or 90 vol% or more.

[0054] 1 is a schematic SEM image of a granular particle according to an embodiment of the present invention. Referring to FIG 1, a surface region with a high binder content was observed from the surface of the granule to a certain depth toward the center of the particle, and the binder distribution was less in the other part than the surface region, i.e., the central part (core part) surrounded by the surface region.

[0055] To describe the granule in more detail, the granule may have a central portion including a plurality of electrode active materials, and a surface portion including an electrode binder located on all or a part of the outside of the central portion and binding the electrode active materials. That is, in the central portion of the granule, the plurality of electrode active materials are in surface contact, line contact, point contact, or contact with two or more of these to form an aggregate, and in the surface portion of the granule, an electrode binder is located on all or a part of the outside of such an aggregate to fix and bind the plurality of electrode active materials in the central portion of the granule to each other.

[0056] According to an embodiment of the present invention, the center portion may further include a small amount of electrode binder to connect and fix the plurality of electrode active materials in the center portion to each other. However, as described above, it is preferable that the content of the electrode binder is higher in the surface portion than in the center portion.

[0057] Meanwhile, in one embodiment of the present invention, the granule may have an aspect ratio of 0.5 to 1.0, preferably 0.75 to 1.0. The aspect ratio may mean the ratio between the length of the short axis and the length of the long axis of the granule. In yet another embodiment of the present invention, the average aspect ratio of the granule may have a value of 0.5 to 1.0, preferably 0.75 to 1.0, in which case, the average aspect ratio may mean the ratio between the average length of the long axis and the average length of the short axis of the granular particles. In this case, the average length of the short axis may mean the average length of the granule in the axial direction having the shortest length, and the average length of the long axis may mean the average length of the granule in the axial direction having the longest length. When the aspect ratio of the granule satisfies such a range, it is advantageous in terms of having sufficient fluidity suitable for the process.

[0058] Meanwhile, in one embodiment of the present invention, the particle size of the granules may be in the range of 0.1 μm to 1,000 μm based on the longest diameter of the particle. In yet another embodiment of the present invention, the average particle size D50 of the granules may be in the range of 0.1 to 1,000 μm.

[0059] <Dry electrodes> An electrode according to one aspect of the present invention is an electrode for an electrochemical device, comprising a current collector and an electrode active material layer located on the current collector. The electrode active material layer is formed by accumulating granules containing an electrode active material and an electrode binder and having the above-mentioned structural characteristics in a layered structure by pressure. The electrode active material layer and the current collector will be described in more detail below.

[0060] <Electrode active material layer> The electrode active material layer includes an electrode active material and an electrode binder. In the present invention, the electrode active material layer may have a form in which the granules are compressed and accumulated in a layered structure. When the granules are introduced into an electrode, the aspect ratio and particle size range may not be maintained in the initial state by a calendaring process described below. The electrode active material layer may include 80 wt% or more, 90 wt% or more, 95 wt% or more, or 99 wt% or more of the granules relative to 100 wt% of the electrode active material layer. Meanwhile, in one embodiment, the electrode active material layer may further include an electrode active material, an electrode binder, an electrode conductive material, etc. that are granulated and exist in a free state without being contained in the granules. Alternatively, the electrode active material layer may further include granular particles whose aspect ratio and / or particle size range are not within the above-mentioned ranges.

[0061] The electrode active material layer has pores due to interstitial volumes between the granules, and exhibits porous properties derived from such a structure. In one embodiment of the present invention, the electrode active material layer preferably has a porosity of 20 vol% to 40 vol%, taking into consideration electrolyte impregnation, dimensional stability, ionic conductivity, and the like.

[0062] Meanwhile, according to one embodiment of the present invention, the thickness of the electrode active material layer may be, for example, 30 μm to 300 μm, but is not limited thereto.

[0063] According to yet another embodiment of the present invention, the electrode active material layer may be formed as a single layer including one unit active material layer.

[0064] According to another embodiment of the present invention, the electrode active material layer may have a multi-layer structure in which two or more unit active material layers are stacked. In this case, the electrode materials, for example, the electrode active material and the electrode binder, contained in each unit active material layer may be the same or different for each layer, but are not limited thereto. In addition, if necessary, each layer may include an electrode conductive material, and in this case, the electrode conductive materials of each layer may be the same or different from each other.

[0065] <Electrode active material layer> In one embodiment of the present invention, the electrode active material layer has a uniform distribution of the binder in the thickness direction. In a specific embodiment, the electrode active material layer may have a difference of 10 wt% or less between the binder content (wt%) at the upper 100 wt% and the binder content (wt%) at the lower 100 wt% in the upper and lower parts of the electrode active material layer based on a point 50% from the current collector. In addition, the difference of 10 wt% or less between the binder content in a region up to 15% of the thickness from the current collector toward the surface layer of the electrode and the binder content in a region up to 15% of the thickness from the surface layer of the electrode active material layer toward the current collector may be.

[0066] Such a distribution of the binder may be due to the fact that the electrode active material layer according to the present invention is manufactured by compressing the granules. As described below, the method for manufacturing an electrode according to the present invention is characterized in that after manufacturing granular particles containing an electrode material, the granular particles are spread on a current collector and compressed, so that the granules are accumulated in a layered structure. In the case of a method for manufacturing an electrode involving the manufacture of a slurry, the migration of the binder is induced by the evaporation of the solvent when the slurry is dried, and the binder is distributed intensively on the surface of the electrode. However, in the present invention, the method of compressing and accumulating dry granules without using a solvent is applied, so that the migration phenomenon of the binder does not occur. Therefore, the binder is uniformly distributed in the thickness direction in each unit layer.

[0067] <Electrode material> According to one embodiment of the present invention, the electrode active material layer may include an electrode active material and an electrode binder, and may further include an electrode conductive material, if necessary. For example, the electrode active material, the electrode conductive material, and the electrode binder may be mixed in a weight ratio of 80 to 99 parts by weight: 0.5 to 10 parts by weight: 0.5 to 10 parts by weight, more specifically, 90 to 99 parts by weight: 0.5 to 5 parts by weight: 0.5 to 10 parts by weight.

[0068] The electrode can be a positive electrode or a negative electrode. When the electrode is a positive electrode, the positive electrode active material is not limited as long as it is in the form of a lithium transition metal oxide or lithium metal iron phosphate, or a metal oxide. For example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), and other layered compounds or compounds substituted with one or more transition metals; 1+x Mn 2-x Lithium manganese oxides such as LiMnO3, LiMn2O3, and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiV3O4, V2O5, and Cu2V2O7; and the chemical formula LiNi 1-x M xNi-site type lithium nickel oxide represented by O2 (where M = Co, Mn, Al, Cu, Fe, Mg, B or Ga and x = 0.01 to 0.3); chemical formula LiMn 2-x M x Lithium manganese composite oxide represented by O2 (where M = Co, Ni, Fe, Cr, Zn or Ta and x = 0.01 to 0.1) or Li2Mn3MO8 (where M = Fe, Co, Ni, Cu or Zn); a part of Li in the chemical formula is substituted by aluminum ions, Li 1+x (Ni a Co b MncAl d ) 1-x O2 (x = 0 to 0.03, a = 0.3 to 0.95, b = 0.01 to 0.35, c = 0.01 to 0.5, d = 0.001 to 0.03, a + b + c + d = 1); lithium metal phosphate LiMPO4 (where M is Fe, CO, Ni or Mn), disulfide compound; examples include Fe2(MoO4)3, but are not limited thereto.

[0069] In another embodiment of the present invention, when the electrode is used as a negative electrode, the electrode active material can be a negative electrode active material. The negative electrode active material is, for example, carbon such as non-graphitizable carbon, graphite-based carbon such as natural graphite and artificial graphite; Li x Fe2O3 (0 ≦ x ≦ 1), Li x WO2 (0 ≦ x ≦ 1), Sn x Me 1-x Me’ y O z (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, Group 1, Group 2, Group 3 elements of the periodic table, halogen; 0 < x ≦ 1; 1 ≦ y ≦ 3; 1 ≦ z ≦ 8) and other metal composite oxides; lithium metal; lithium alloy; silicon-based alloy; tin-based alloy; silicon-based oxides such as SiO, SiO / C, SiO2; metal oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4 and Bi2O5; conductive polymers such as polyacetylene; Li-Co-Ni-based materials, etc. can be used, but are not limited thereto.

[0070] In one embodiment of the present invention, the granular particles may contain two or more different electrode active materials within one particle. The electrode active materials are not particularly limited as long as they are the above-mentioned components. For example, the granules may contain artificial graphite and natural graphite as electrode active materials, or the artificial graphite and natural graphite may be mixed in a predetermined ratio.

[0071] The electrode conductive material is not particularly limited as long as it has conductivity without inducing a chemical change in the battery. For example, graphite such as natural graphite or artificial graphite; carbon black such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fiber such as carbon fiber or metal fiber; metal powder such as carbon fluoride, aluminum, and nickel powder; conductive whisker such as zinc oxide and potassium titanate; conductive metal oxide such as titanium oxide; conductive material such as polyphenylene derivatives, etc. may be used. In detail, in order to uniformly mix the electrode conductive material and improve conductivity, one or more selected from the group consisting of activated carbon, graphite, carbon black, and carbon nanotubes may be included. More specifically, activated carbon may be included. Meanwhile, in one embodiment of the present invention, the granular particles may contain two or more different conductive materials within one particle. For example, the granules may be a mixture of carbon black and carbon nanotubes as conductive materials in a predetermined ratio.

[0072] In the present invention, the electrode binder is not particularly limited as long as it is used as a binder material for electrochemical elements, and may include, for example, a diene-based polymer, an acrylate-based polymer, a fluorine-based polymer, a styrene-based polymer, or two or more of these.

[0073] Examples of the diene polymer include polymers containing monomer units derived from conjugated dienes such as butadiene and isoprene, and hydrogenated products thereof. The proportion of the monomer units derived from conjugated dienes in the diene polymer is usually 40 wt% or more, preferably 50 wt% or more, and more preferably 60 wt% or more.

[0074] Specific examples include conjugated diene homopolymers such as polybutadiene or polyisoprene; aromatic vinyl-conjugated diene copolymers such as styrene-butadiene copolymer (SBR) which may be carboxy-modified; cyanide vinyl conjugated diene copolymers such as acrylonitrile-butadiene copolymer (NBR); hydrogenated SBR, hydrogenated NBR, etc.

[0075] The styrene-based polymer is a polymer having a repeating unit derived from a styrene monomer, and examples thereof include styrene homopolymer (polystyrene), styrene copolymer, etc. Examples of the styrene copolymer include block copolymers such as styrene-ethylene-butadiene copolymer, styrene-butadiene-propylene copolymer, styrene-isoprene copolymer, styrene-n-butyl acrylate-itaconic acid-methyl methacrylate-acrylonitrile copolymer, styrene-n-butyl acrylate-itaconic acid-methyl methacrylate-acrylonitrile copolymer, styrene-butadiene block copolymer, styrene-butadiene-styrene block copolymer, styrene-ethylene-butylene-styrene block copolymer, styrene-isoprene block copolymer, and styrene-ethylene-propylene-styrene block copolymer.

[0076] Examples of the acrylate polymer include polymers containing monomer units derived from acrylic acid esters and / or methacrylic acid esters. The proportion of monomer units derived from acrylic acid esters and / or methacrylic acid esters in the acrylate polymer is usually 40 wt% or more, preferably 50 wt% or more, and more preferably 60 wt% or more. Specific examples of acrylate polymers include crosslinked acrylate polymers such as 2-ethylhexyl acrylate-methacrylic acid-acrylonitrile-ethylene glycol dimethacrylate copolymer, 2-ethylhexyl acrylate-methacrylic acid-methacrylonitrile-ethylene glycol dimethacrylate copolymer, 2-ethylhexyl acrylate-styrene-methacrylic acid-ethylene glycol dimethacrylate copolymer, butyl acrylate-acrylonitrile-diethylene glycol dimethacrylate copolymer, and butyl acrylate-acrylic acid-trimethylolpropane trimethacrylate copolymer; copolymers of ethylene and (meth)acrylic acid ester such as ethylene-methyl acrylate copolymer, ethylene-methyl methacrylate copolymer, ethylene-ethyl acrylate copolymer, and ethylene-ethyl methacrylate copolymer; polymers obtained by grafting a radical polymerizable monomer onto the copolymer of ethylene and (meth)acrylic acid ester; and the like. Examples of radical polymerizable monomers used in the graft polymers include methyl methacrylate, acrylonitrile, and methacrylic acid. In addition, copolymers of ethylene and (meth)acrylic acid, such as ethylene-acrylic acid copolymer and ethylene-methacrylic acid copolymer, can be used as the dispersion type binder.

[0077] The fluoropolymer may include polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), polyvinylidene fluoride copolymer such as PVDF-HFP, etc. In particular, it may include polytetrafluoroethylene (PTFE), and more particularly, it may be polytetrafluoroethylene (PTFE).

[0078] Meanwhile, in one embodiment of the present invention, the granular particles may contain two or more different binder materials within one particle. For example, the granules may be a mixture of styrene-butadiene rubber (SBR) and an acrylate polymer in a predetermined ratio as binder materials.

[0079] In one embodiment of the present invention, when the electrode is a positive electrode, the positive electrode binder may include a fluorine-based copolymer. In a specific embodiment, the positive electrode fluorine-based copolymer may include PTFE, and more preferably, PTFE may be included in an amount of 60 wt% or more based on the total weight of the binder. Of course, the positive electrode binder may further include a fluorine-based copolymer other than PTFE, a styrene-based copolymer, a polyolefin-based copolymer, PEO (polyethylene oxide), an acrylate-based copolymer, etc.

[0080] Meanwhile, in one embodiment of the present invention, when the electrode is a negative electrode, the negative electrode binder may include at least one of a diene-based copolymer and a styrene-based polymer, and may be included in an amount of 60 wt% or more based on the total weight of the binder. In a specific embodiment, the negative electrode styrene-butadiene block copolymer may be included in an amount of 60 wt% or more based on the total weight of the binder. Meanwhile, the negative electrode binder may further include a fluorine-based copolymer, a polyolefin-based copolymer, PEO (polyethylene oxide), an acrylate-based copolymer, and the like.

[0081] Meanwhile, according to an embodiment of the present invention, when the electrode binder includes an electrode binder having a double bond, for example, when the electrode is a negative electrode, the negative electrode active material layer may have a first Quantified Binder Ratio (QBR) of 2.0 or less.

[0082] The first QBR is defined by the following mathematical formula: 1st QBR=ABs / ABf

[0083] In the above mathematical formula, ABs represents an average value of the double bond content in a surface region of the negative electrode active material layer from the outermost surface of the negative electrode active material layer to within 15% of the total thickness of the negative electrode active material layer, and ABf represents an average value of the double bond content in a bottom region of the negative electrode active material layer from the interface of the negative electrode active material layer facing the current collector to within 15% of the total thickness of the negative electrode active material layer.

[0084] 6 is a schematic diagram of an electrode according to an embodiment of the present invention. Referring to FIG 6, an electrode 10 includes an electrode current collector 12 and an electrode active material layer 11 disposed on the electrode current collector 12 and including an electrode active material and a fluorine-containing electrode binder.

[0085] The electrode active material layer 11 has a surface region 11s of the electrode active material layer that extends from the outermost surface of the electrode active material layer to within 15% of the total thickness d of the electrode active material layer, and a bottom region 11f of the electrode active material layer that extends from the interface of the electrode active material layer that faces the electrode current collector to within 15% of the total thickness d of the electrode active material layer, based on the total thickness d.

[0086] In the first QBR formula, ABs means the average value of the double bond content of the binder in the surface region 11s of the electrode active material layer, and ABf means the average value of the double bond content of the binder in the bottom region 11f of the electrode active material layer.

[0087] In this case, the first QBR can be calculated in the following manner. First, an electrode for which the first QBR is to be confirmed is selected, and a cross section of the selected negative electrode is prepared using Ar ion milling. Then, the components in the negative electrode active material layer of the prepared electrode cross section are EDS mapped using an Energy Dispersive X-ray Spectroscopy (EDS) detector of a Scanning Electron Microscope (SEM) device.

[0088] From the EDS mapping results, a line profile is extracted in the thickness direction of the negative electrode active material layer. From the extracted line profile results, an average value Bs of the double bond content of the binder in the surface region of the electrode layer and an average value Bf of the double bond content of the binder in the bottom region of the electrode layer are extracted, and a first QBR value is calculated using the following formula. 1st QBR=ABs / ABf

[0089] In this case, the surface region of the electrode active material layer is a region from the outermost surface in the thickness direction of the electrode active material layer to within 15% of the total thickness of the electrode active material layer, and the bottom region of the electrode active material layer is a region from the interface of the electrode active material layer facing the current collector to within 15% of the total thickness of the electrode active material layer.

[0090] FIG. 7 is a schematic diagram for calculating the first QBR value of the electrode active material layer. Referring to FIG. 7, the X-axis indicates the thickness of the electrode active material layer, i.e., the distance from the surface toward the current collector, and the Y-axis indicates the intensity of the fluorine component. Line A indicates the intensity of the double bond component of the binder having a double bond extracted by EDS mapping the double bond component in the electrode active material layer of the electrode cross section, and line B is a trend line showing the tendency of line A, which is a line smoothed by the LOWESS smoothing method, i.e., the locally weighted scatterplot smoother method. In FIG. 7, Bs indicates the strength of the binder in the electrode surface portion, and Bf indicates the strength of the binder in the lower part of the electrode (current collector facing portion).

[0091] The first QBR value is a value indicating the uniformity of the electrode binder distributed in the thickness direction in the electrode active material layer based on the ratio of the content of the electrode binder contained in the surface region to the content of the electrode binder contained in the bottom region of the electrode active material layer, where the content of the electrode binder can be inferred from the double bond component contained in the electrode binder used.

[0092] The first QBR value may be 2.0 or less, or 0.6 to 2.0, or 0.9 to 2.0, or 0.6 to 1.4, or 0.6 to 1.4, or 0.9 to 1.4, or 0.9 to 1.1.

[0093] When the first QBR satisfies such a range, the binder migrates to the electrode surface, and the content of the electrode binder contained in the surface region of the electrode active material layer is not large compared to the content of the electrode binder contained in the bottom region of the electrode active material layer, and the distribution of the binder in the thickness direction of the electrode active material layer is uniform. As a result, the adhesion between the current collector and the electrode active material layer is improved, and the conductivity at the surface of the electrode active material layer and the charge / discharge rate therewith can also be increased, which is advantageous.

[0094] Meanwhile, in one embodiment of the present invention, the negative electrode may include a negative electrode binder having a double bond as a binder material, such as a styrene-butadiene copolymer, in which case the second QBR value may be 2.0 or less.

[0095] According to an embodiment of the present invention, when the electrode includes a fluorine-based binder as a binder material, for example, when the electrode is a positive electrode, the positive electrode active material layer has a second Quantified Binder Ratio (QBR) of 1.1 or less, and the second QBR may be defined by the following mathematical formula: Second QBR = CBs / CBf

[0096] In the above mathematical formula, CBs represents the average value of the fluorine content of the electrode binder in a surface region of the electrode layer from the outermost surface of the electrode active material layer to within 15% of the total thickness of the electrode layer, and CBf represents the average value of the fluorine content of the electrode binder in a bottom region of the electrode active material layer from the interface of the electrode active material layer facing the electrode current collector to within 15% of the total thickness of the electrode active material layer.

[0097] The first QBR value is 1.1 or less, and according to one embodiment of the present invention, the first QBR value may be 0.95 or more, 0.97 or more, 1.03 or less, 1.05 or less, or may be 0.95 to 1.05.

[0098] When the first QBR value is in the range of 1.1 or less, the fluorine-containing electrode binder migrates to the electrode surface, and the content of the fluorine-containing electrode binder contained in the surface region of the electrode active material layer is not large compared to the content of the fluorine-containing electrode binder contained in the bottom region of the electrode active material layer, and the distribution of the binder in the thickness direction of the electrode active material layer is uniform. As a result, the adhesion between the current collector and the electrode active material layer is improved, and the electrical conductivity at the surface of the electrode active material layer and the charge / discharge rate therefor can also be increased, which is advantageous.

[0099] In one embodiment of the present invention, the positive electrode may contain a fluorine-based binder resin, and in this case, the first QBR value may be 1.1 or less.

[0100] Meanwhile, in the present invention, the electrode binder may include a diene-based polymer and a crosslinked acrylate-based polymer, in that an active material layer having excellent adhesion to a current collector and surface smoothness can be obtained, and an electrode for an electrochemical device having high capacitance and low internal resistance can be manufactured.

[0101] The shape of the electrode binder is not particularly limited, but it is desirable that the electrode binder is granular because it has good binding properties and can suppress the decrease in the capacitance of the electrode produced and the deterioration due to repeated charging and discharging. Examples of granular electrode binders include those in which dispersed binder particles are dispersed in water, such as latex, and powder-like ones obtained by drying such a dispersion. Such granular binders can be desirably included in the negative electrode.

[0102] In some cases, the electrode active material layer may further contain a filler, which is a component that suppresses the expansion of the electrode active material layer, and the filler is not particularly limited as long as it does not induce chemical changes in the battery and is a fibrous material. For example, olefin polymers such as polyethylene and polypropylene, and fibrous materials such as glass fiber and carbon fiber are used.

[0103] The current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, copper, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. may be used. In addition, the current collector may have fine irregularities on its surface to increase the adhesive strength of the electrode active material, and may be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0104] Meanwhile, in one embodiment of the present invention, the current collector may be entirely or partially coated with a conductive primer.

[0105] The primer layer includes a binder for the primer layer (hereinafter, the second binder) and a conductive material for the primer layer (hereinafter, the second conductive material), and the sum of the contents of the second binder and the second conductive material in the primer layer may be 90 wt% or more.

[0106] An electrode according to an embodiment of the present invention includes an electrode active material layer including granules, and in this case, a primer layer including a second binder and a second conductive material, the sum of the contents of the second binder and the second conductive material being 90 wt% or more, thereby ensuring the stability of the primer layer over time, and thus exhibiting excellent physical properties such as adhesive strength and life characteristics, but the present invention is not limited thereto.

[0107] According to one embodiment of the present invention, the primer layer includes a second binder and a second conductive material, and may further include a dispersant.

[0108] According to another embodiment of the invention, the primer layer includes a second binder and a second conductive material, but may be substantially free of a dispersant.

[0109] According to an embodiment of the present invention, the second binder may be any binder known to be used in a primer layer without any particular limitation.

[0110] According to another embodiment of the present invention, the second binder may be a polymer capable of ensuring stability over time of the primer layer, and more specifically, the second binder may have a glass transition temperature (Tg) of 45° C. or less.

[0111] According to another embodiment of the present invention, the second binder may be, for example, styrene butadiene rubber (SBR), butadiene rubber (BR), nitrile butadiene rubber (NBR), styrene butadiene styrene block polymer (SBS), styrene ethylene butadiene block polymer (SEB), styrene-(styrene butadiene)-styrene block polymer, natural rubber (NR), isoprene rubber (IR), ethylene-propylene-diene terpolymer (EPDM), poly(ethylene-co-propylene-co-5-methylene-2-norbornene), polytetrafluoroethylene (PTFE), polyvinylidene fluoride, polyvinyl chloride, polyvinylidene fluoride-hexafluoropropylene ... The polymer may include polyvinyl fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polymethylmethacrylate, polyethylhexylacrylate, polybutylacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinylacetate, polyethylene, polypropylene, ethylene-vinyl acetate, polyethylene oxide, polypropylene oxide, polyarylate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, or two or more thereof.Specifically, the binder may include styrene butadiene rubber (SBR), nitrile butadiene rubber (NBR), polymethylmethacrylate, polyethylhexylacrylate, polybutylacrylate, or two or more thereof.

[0112] According to yet another embodiment of the present invention, the second binder has the above-mentioned glass transition temperature value and may be one or a mixture of two or more selected from the above-mentioned types.

[0113] According to yet another embodiment of the present invention, the second binder may be a styrene butadiene rubber (SBR) having a glass transition temperature Tg of -40°C to 45°C, a nitrile butadiene rubber (NBR) having a glass transition temperature Tg of -40°C to 45°C, or a mixture thereof.

[0114] According to one embodiment of the present invention, the specific surface area of ​​the second conductive material is 30 m 2 / g~1,400m 2 / g and may be spherical. In this case, the size of the primary particles of the spherical conductive material may be, for example, 10 nm to 100 nm, specifically 15 nm to 70 nm, but is not limited thereto.

[0115] According to another embodiment of the present invention, the second conductive material has a specific surface area of ​​10 m 2 / g~400m 2 In this case, the diameter of the cross section of the tubular conductive material in the direction perpendicular to the longitudinal direction may be 0.1 nm to 3 nm, specifically 0.3 nm to 1.5 nm, but is not limited thereto.

[0116] The second conductive material is not particularly limited as long as it does not induce a chemical change in the battery and has conductivity. For example, graphite such as natural graphite or artificial graphite; carbon black-based carbon compounds such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives may be used. In particular, in order to uniformly mix the conductive material and improve conductivity, the second conductive material may include activated carbon, graphite, carbon black, carbon nanotubes, or a mixture of two or more of these, and more particularly, may include activated carbon.

[0117] According to an embodiment of the present invention, the primer layer may have the above-mentioned composition and a thickness of 300 nm to 1.5 μm, specifically, 700 nm to 1.3 μm, but is not limited thereto.

[0118] <Granule manufacturing method> According to an embodiment of the present invention, the granules included in the active material layer may be prepared by a method including: preparing a slurry by mixing an electrode active material and an electrode binder with a dispersion medium; and spray-drying the slurry.

[0119] First, the electrode active material and electrode binder, and optionally additional conductive materials and additives, are dispersed or dissolved in a dispersion medium (solvent for the negative electrode binder) to obtain a slurry in which the electrode conductive material and / or other additives are dispersed or dissolved together with the electrode active material and electrode binder.

[0120] The dispersion medium used to obtain the slurry is most preferably water, but an organic solvent may be used. Examples of organic solvents include alkyl alcohols such as methyl alcohol, ethyl alcohol, and propyl alcohol; alkyl ketones such as acetone and methyl ethyl ketone; ethers such as tetrahydrofuran, dioxane, and diglyme; amides such as diethylformamide, dimethylacetamide, N-methyl-2-pyrrolidone (hereinafter also referred to as NMP), and dimethylimidazolidinone; sulfur-based solvents such as dimethyl sulfoxide and sulfolane; and the like, with alcohols being preferred. The combined use of an organic solvent with a boiling point lower than that of water can increase the drying speed during fluidized granulation. In addition, the dispersibility or solubility of the negative electrode binder can change, so that the viscosity and fluidity of the slurry can be adjusted according to the amount or type of the dispersion medium, thereby improving production efficiency.

[0121] The amount of dispersion medium used when preparing the slurry may be an amount such that the solids concentration of the slurry is usually in the range of 1 wt% to 50 wt%, or 5 wt% to 50 wt%, or 10 wt% to 30 wt%.

[0122] The method or order of dispersing or dissolving the electrode active material and electrode binder in the dispersion medium is not particularly limited, and examples thereof include a method of adding the electrode active material and electrode binder to the dispersion medium and mixing them, and a method of dissolving or dispersing the electrode binder in the dispersion medium and then adding the electrode active material and mixing them. When the slurry contains a conductive material and / or additives, these components may be added when the electrode active material is added. Examples of mixing means include mixing devices such as a ball mill, a sand mill, a bead mill, a pigment disperser, a stone mill, an ultrasonic disperser, a homogenizer, and a planetary mixer. Mixing may be performed, for example, at room temperature to 80° C. for 10 minutes to several hours.

[0123] Next, the slurry is spray-dried. The spray drying method is a method of spraying the slurry into hot air and drying it. Examples of the spraying method of the device used in the spray drying method include the rotating disk method and the nozzle pressurization method. The rotating disk method is a method in which the slurry is introduced almost at the center of a disk rotating at high speed, and when the slurry comes off the disk due to the centrifugal force of the disk, it is atomized and dried. The rotation speed of the disk depends on the size of the disk, but is usually 5,000 rpm to 35,000 rpm, preferably 15,000 rpm to 30,000 rpm. On the other hand, the nozzle pressurization method is a method in which the slurry is passed through a thin nozzle, and a high-pressure fluid such as air or other liquid is sprayed together with the slurry to spray it into a mist and dry it.

[0124] In one embodiment of the present invention, the temperature of the hot air may be controlled to 80°C to 250°C based on the temperature of the inlet of the reactor (at the time of introduction) in terms of forming a granular structure with a high content of electrode binder on the surface. In the present invention, the temperature may be controlled to preferably 175°C to 220°C, more preferably 180°C to 220°C, taking into consideration the gradient of the binder content and the aspect ratio. In the spray drying method, the method of inhaling the hot air is not particularly limited, and examples thereof include a method in which the hot air and the spray direction flow sideways in parallel, a method in which the hot air is sprayed from the top of the drying tower and falls together with the hot air, a method in which the sprayed droplets and the hot air come into countercurrent contact, and a method in which the sprayed droplets flow sideways with the initial hot air and then fall by gravity to come into countercurrent contact. Meanwhile, in one embodiment of the present invention, the outlet temperature of the reactor (the temperature of the hot air discharged from the reactor) during the spray drying may be controlled to 90°C to 130°C.

[0125] If the outlet temperature and / or ΔT, which is the difference between the inlet temperature and the outlet temperature, is low, the drying is not sufficient, and particles with a large amount of residual solvent are formed, and uniform spherical particles are not produced, and the granules may aggregate or be formed in an irregular state. On the other hand, if the inlet temperature is too high and ΔT is large, the granules are not granulated due to over-drying, and particles with a very small D50 and a low aspect ratio may be produced. Therefore, in order to control the particle size to an appropriate level with a high aspect ratio and little binder aggregation, it is necessary to control the inlet temperature and outlet temperature within an appropriate range.

[0126] Optionally, the product obtained by spray drying, i.e., the granules, may be heat-treated to harden the surface thereof. In this case, the heat-treatment temperature may be generally 80°C to 300°C.

[0127] <Electrode manufacturing method> According to an embodiment of the present invention, a method for manufacturing an electrode includes the steps of: dispersing a plurality of granules on a current collector; and compressing the dispersed granules to form an electrode active material layer.

[0128] The granules prepared by the above method are spread on a current collector, and at least one surface of the current collector may be provided with a primer layer including the second conductive material and the second binder as described above.

[0129] According to an embodiment of the present invention, the prepared granules can be fed to a roll-type pressure molding device by a feeder such as a screw feeder to form an active material layer, and in this case, the current collector can be fed to the roll of the pressure molding device at the same time as the granules are fed, so that the active material layer can be directly laminated on the current collector. Alternatively, the granules can be spread on the current collector, and the thickness can be adjusted to a uniform level using a blade or the like, and then the electrode active material layer can be formed by molding using a pressure device.

[0130] In these methods, the temperature during roll pressure molding is usually 0°C to 200°C, and is preferably higher than the melting point or glass transition temperature of the electrode binder, and more preferably 20°C or more higher than the melting point or glass transition temperature. The molding speed in roll pressure molding can usually be 0.1 m / min to 20 m / min, or 1 m / min to 10 m / min. The linear pressure of the press between the rolls can usually be 0.2 kN / cm to 30 kN / cm, or 0.5 kN / cm to 10 kN / cm.

[0131] In order to eliminate the variation in thickness of the formed electrode and increase the density of the electrode active material layer to increase the capacity, a pressurization process may be performed as necessary. The post-pressurization method is generally a press process using rolls. In the roll press process, two cylindrical rolls are set up parallel to each other with a narrow gap between them and rotated in opposite directions to sandwich the electrode between them and pressurize it. The temperature of the rolls may be adjustable by heating or cooling, for example.

[0132] According to another embodiment of the present invention, there is provided a secondary battery in which an electrode assembly including the positive electrode, the negative electrode, and the separator is housed in a battery case (cylindrical case, prismatic case, pouch, etc.) together with a lithium-containing non-aqueous electrolyte, and an energy storage device including the same as a unit battery, in which at least one of the positive electrode and the negative electrode may be the above-mentioned electrode.

[0133] The separator may be a conventional porous polymer film used in the prior art, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, or an ethylene / methacrylate copolymer, either alone or in combination. Also, a thin insulating membrane having high ion permeability and mechanical strength may be used. The separator may include a safety reinforced separator (SRS) in which a ceramic material is thinly coated on the surface of the separator. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high melting point glass fiber, polyethylene terephthalate fiber, or the like, may be used, but is not limited thereto.

[0134] The electrolytic solution contains a lithium salt as an electrolyte and an organic solvent for dissolving the lithium salt. The lithium salt can be used without any limitation as long as it is one that is commonly used in electrolytes for secondary batteries. For example, the anion of the lithium salt is F - , Cl - , I - , NO3 - , N(CN)2 -, BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - One selected from the group consisting of:

[0135] The organic solvent contained in the electrolytic solution may be any commonly used organic solvent without limitation. Representative examples thereof include at least one selected from the group consisting of propylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, dipropyl carbonate, dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, vinylene carbonate, sulfolane, γ-butyrolactone, propylene sulfide, and tetrahydrofuran.

[0136] In particular, ethylene carbonate and propylene carbonate, which are cyclic carbonates among the carbonate-based organic solvents, are preferably used since they are high-viscosity organic solvents with high dielectric constants and can easily dissociate lithium salts in the electrolyte. When such cyclic carbonates are mixed with chain carbonates having low viscosity and low dielectric constants, such as dimethyl carbonate and diethyl carbonate, in an appropriate ratio, an electrolyte solution having high electrical conductivity can be prepared, which can be more preferably used.

[0137] Optionally, the electrolyte stored according to the present invention may further contain additives such as overcharge inhibitors that are typically included in electrolytes.

[0138] In the lithium secondary battery according to an embodiment of the present invention, a separator is disposed between a positive electrode and a negative electrode to form an electrode assembly, and the electrode assembly is placed in, for example, a pouch, a cylindrical battery case, or a prismatic battery case, and an electrolyte is injected to complete the secondary battery. Alternatively, the electrode assemblies may be stacked, impregnated with an electrolyte, and the resulting product may be placed in a battery case and sealed to complete the lithium secondary battery.

[0139] At this time, the specific structures of the secondary battery and the energy storage device are the same as those conventionally known, and therefore, description thereof will be omitted in this specification.

[0140] The present invention will be described below with reference to specific examples. However, the examples according to the present invention can be modified into many other forms, and the scope of the present invention should not be construed as being limited to the following examples. The examples of the present invention are provided to more completely explain the present invention to those having ordinary skill in the art.

[0141] Working Example [Example 1] 1.Negative electrode (1) Preparation of current collector with primer layer Secondary conductive carbon black (specific surface area: 30 m 2 / g, particle size: 70 nm), 30 parts by weight, styrene-butadiene rubber (SBR) as a second binder (T g The slurry for the primer layer was prepared by mixing 69 parts by weight of ethylenediaminetetraacetate (ethylenediaminetetraacetate) (at -15°C) and 1 part by weight of carboxymethylcellulose (CMC) as a dispersant with water as a dispersion medium. The content ratio of the conductive material, binder, and dispersant in the slurry was the same as the content ratio of the conductive material, binder, and dispersant in the primer layer to be formed later. The solid content of the slurry for the primer layer was 7 wt%.

[0142] The prepared primer layer slurry was applied to one surface of a copper current collector (thickness: 10 μm) and dried at 130° C. to form a primer layer on the surface of the copper current collector.

[0143] (2) Preparation of granules for negative electrode active material As the negative active material, 1.91 parts by weight of natural graphite with a sphericity of 0.95 and 76.5 parts by weight of artificial graphite with an average sphericity of 0.9, carbon black (Super C65) as the negative conductive material, carboxymethylcellulose (daicel 2200, aqueous solution form, solid content concentration 1.5 wt%) as the negative dispersant, and modified styrene butadiene copolymer (Grade Name AX-B119) as the negative binder were mixed in a weight ratio of 95.6:1.0:1.1:2.3 with water as the dispersion medium to prepare a slurry with a viscosity of about 1,000 cPs using a homogenizer. At this time, the solid content of the slurry was 30 wt%. In the above weight ratio, the carboxymethylcellulose was calculated based on the solid content.

[0144] The prepared slurry was dried by feeding it into a spray dryer together with hot air under pressure conditions of -40 mmH2O. The conditions of the spray dryer were controlled as follows: inlet temperature 180°C, outlet temperature 90°C, and rotation speed 18,000 rpm. The obtained granules were sieved to remove coarse powder of 150 μm or more, and fine powder of less than 40 μm was further separated. The separated fine powder was mixed with the granules from which only the coarse powder was removed, to finally prepare anode granules containing a larger amount of fine powder than the previous granules. The granules had a center portion containing a plurality of anode active materials and anode conductive materials, and a surface portion located outside the center portion and containing anode binder binding the anode active materials and anode conductive materials. The obtained granules had an average particle size D50 of 66.5 μm and an aspect ratio of 0.96. 8 shows a cross-sectional image of the granular particles prepared in Example 1, which was processed by EPMA (electron probe micro analysis) to be described later. The closed curve shown in the image connects points having the same distance from the surface.

[0145] (3) Manufacturing of negative electrodes The current collector having the primer layer is then heated to a thickness of 25 cm using a thickness adjusting bar. 2 The granules prepared as described above were uniformly applied in an amount of 400 mg per sheet, and pressed at a speed of 2 m / min under conditions of 0.7 ton / cm and 60°C using a roll-to-roll hot rolling molding machine, which is a sheeting machine, to form a negative electrode active material layer, thereby manufacturing a negative electrode.

[0146] [Example 2] Granules were produced in the same manner as in Example 1, except that the inlet temperature of the spray dryer was controlled to 180°C and the outlet temperature was controlled to 130°C. The average particle size D50 of the obtained granules was 61.4 μm and the aspect ratio was 0.99. FIG. 9 is a cross-sectional image of the granular particles produced in Example 2, which was processed using the EPMA method described below. The closed curve shown in the image connects points having the same distance from the surface.

[0147] [Example 3] Granules were produced in the same manner as in Example 1, except that the inlet temperature of the spray dryer was controlled to 200° C. and the outlet temperature was controlled to 110° C. The average particle size D50 of the obtained granules was 35.8 μm and the aspect ratio was 0.77. 10 shows a cross-sectional image of the granular particles prepared in Example 3, processed by the EPMA method described below. The closed curve shown in the image connects points that have the same distance from the surface to the center of the granule.

[0148] [Comparative Example 1] Granules were prepared in the same manner as in Example 1, except that the inlet temperature of the spray dryer was controlled to 170°C and the outlet temperature was controlled to 70°C. The average particle size D50 of the obtained granules was 42.8μm and the aspect ratio was 0.75. In addition, a negative electrode was prepared in the same manner as in Example 1, except that the granules prepared in Comparative Example 1 were used instead of the granules prepared in Example 1. In Comparative Example 1, the granules were somewhat overdried, with an aspect ratio of 0.75 or less, and the particles were not uniformly spherical, and there was a large variation between the particles. FIG. 11 shows a cross-sectional image of the granular particles prepared in Comparative Example 1, which was processed using the EPMA method described below. It was confirmed that the binder resin (light color) was distributed throughout the cross section of the granules. The closed curve shown in the image connects points having the same distance from the surface.

[0149] [Comparative Example 2] Granules were produced in the same manner as in Example 1, except that the inlet temperature of the spray dryer was controlled to 170°C and the outlet temperature was controlled to 140°C. The average particle size D50 of the obtained granules was 78.0 μm and the aspect ratio was 0.37. In Comparative Example 2, the difference between the inlet and outlet temperatures was small, so the solvent was not sufficiently removed, and particles with a large amount of residual solvent were formed, which resulted in the formation of spherical particles with a uniform shape, and the water content was high, resulting in aggregation between particles.

[0150] Figure 12 shows a cross-sectional image of the granular particles produced in Comparative Example 2, processed using the EPMA method described below. It can be seen that the binder resin (light color) is distributed throughout the cross section of the granule. The closed curve shown in the image connects points that are the same distance from the surface.

[0151] [Comparative Example 3] Granules were produced in the same manner as in Example 1, except that the inlet temperature of the spray dryer was controlled to 230° C. and the outlet temperature was controlled to 90° C. In Comparative Example 3, the difference between the inlet temperature and the outlet temperature was large, so that granulation was not performed by over-drying, and it was impossible to produce granules.

[0152] [Comparative Example 4] A slurry with a solid content of 47 wt% was prepared by mixing 19.1 parts by weight of natural graphite with an average sphericity of 0.95 and 76.5 parts by weight of artificial graphite with an average sphericity of 0.9 as the negative electrode active material, 1 part by weight of carbon black (Super-C 65) as the negative electrode conductive material, 2.3 parts by weight of styrene butadiene rubber (SBR) as the negative electrode binder, 1.1 parts by weight of carboxymethyl cellulose (CMC) as a binder and thickener, and water as a dispersion medium.

[0153] The slurry was coated on one side of a copper (Cu) thin film, which was a negative electrode current collector with a thickness of 10 μm, and the upper and lower active material layers thus formed were simultaneously rolled by roll pressing using a drying device equipped with a hot air blower and an IR heater, resulting in a dry weight per unit area of ​​400 mg / 25 cm. 2 A negative electrode having a negative electrode active material layer with a loading amount of 1000g / m2 was prepared.

[0154] Checking the distribution of binder in granules The radial profile of the cross section of the granules was analyzed using EPMA (JXA-8350F, -15 kV, 20 nA stage mapping conditions) to confirm the binder distribution in the granules. First, the binder in each granule obtained in each of Examples 1 to 3 and Comparative Examples 1 and 2 was stained using OsO4. The staining was carried out by placing the granules in each glass container using OsO4 crystals or an aqueous solution, and then evaporating the reagent to react. Then, the granules were mixed with epoxy resin, fixed in a silicon mold, and hardened to obtain a granule matrix (see FIG. 16). Next, a cross section sample was prepared from the granule matrix using an ion milling device (Hitachi IM5000, acceleration voltage: 6 kV). The cross section preparation conditions were an acceleration voltage of 6 kV and an emission current of 400 uA, and the milling time was appropriately adjusted so that the mask was not completely etched. The prepared cross-sectional sample was fixed in the EPMA device, and the granule was placed at the center of the display, and the cross-section was scanned by the stage mapping method. When the scan was completed, an image was prepared in the form of a mass map, taking into consideration the atomic number effect, absorption effect, and fluorescence excitation effect. From the obtained mass map, 0-4 wt% of elements were assigned to a contrast of 0-255 5, and an Os map was extracted. The conventional backscattered electron image and the Os map obtained in the EPMA analysis process were combined into one layer using Photoshop (registered trademark), and then closed curves were drawn in 30 pixel units from the boundary of the granule obtained from this, and the Os content located at each closed curve was analyzed. The Os content was supplemented by introducing the surface area of ​​the closed curve at the corresponding position so that the relative amount at each position can be compared. Figure 13a shows the distribution (content) of the binder resin at each part along the radius of the granules of each Example and Comparative Example. Figure 13b shows the cumulative distribution of the binder resin along the radius of the granules of each Example and Comparative Example. With reference to this, it can be seen that the granules of Examples 1 to 3 have a higher binder content in the surface area up to 70% or more, particularly 80% or more of the granule surface, than in the center area.In contrast, it was confirmed that the granules obtained in Comparative Examples 1 and 2 had a higher binder content in the center than in the surface region.

[0155] Confirmation of the distribution of binder in the negative electrode active material layer The negative electrodes prepared in Example 1 and Comparative Example 4 were thoroughly chemically reacted (deposited) for more than 3 hours by placing them in a glass container together with OsO4 crystals or an aqueous solution and evaporating the reagent. Then, the negative electrodes reacted with Os were milled by argon ion milling to produce cross sections of the negative electrodes of the Examples and Comparative Examples.

[0156] Using an EDS detector of an SEM apparatus, the components in the negative electrode active material layer of the cross section in the thickness direction of the negative electrodes of Example 1 and Comparative Example 4 were subjected to EDS mapping.

[0157] FIG. 2 shows the EDS mapping results of the electrode of Example 1, and FIG. 4 shows the EDS mapping results of the electrode of Comparative Example 4. Referring to these, it was confirmed that the binder resin was distributed more in the surface portion of the granules than in the center portion of the granules in the electrode of Example 1. In addition, it was confirmed that the electrode of Example 1 was manufactured by pressing the granules, and the binder was uniformly distributed in the thickness direction of the electrode. On the other hand, it was confirmed that the electrode of Comparative Example 4 had a high binder content ratio in the surface layer of the electrode. Unlike the manufacturing method of the electrode of Example 1, the electrode of Comparative Example 4 was manufactured by an electrode slurry coating and drying method, and such binder distribution was caused by migration of the binder due to evaporation of the solvent.

[0158] 3 and 5 are graphs each showing an average value of the Os content of the binder bound to Os in the surface region (region up to 15% from the surface toward the current collector) of the negative active material layer, and an average value of the Os content of the binder bound to Os in the bottom region (region up to 15% from the current collector toward the surface layer) of the electrode layer, which are respectively obtained by extracting a line profile in the thickness direction of the negative active material layer from the EDS mapping result. FIG. 3 relates to the electrode of Example 1, and FIG. 5 relates to the electrode of Comparative Example 4. It was confirmed that the deviation of the binder distribution in the thickness direction of the electrode in the electrode of Example 1 was smaller than that in the electrode of Comparative Example 4.

[0159] Check the distribution of electrode load The electrode load was measured for the surface (surface of the negative electrode active material layer, 100 mm x 150 mm size) of the negative electrode prepared in Example 1 and the negative electrode prepared in Comparative Example 1. The surface of each obtained negative electrode was scanned using an inductance measuring device (TSS20, Lasertec). An induced current was applied at a certain distance from the negative electrode, and information on only the negative electrode active material layer formed on the current collector was confirmed. An image showing uniformity was obtained based on the uniformity of the negative electrode active material layer (material distribution, thickness, porosity, etc.). According to the confirmation, it was confirmed that the negative electrode of Example 1 showed a uniform negative electrode active material load amount over the surface of the negative electrode, while the negative electrode of Comparative Example 1 had a difference in the load amount between the left and right sides of the negative electrode. FIG. 14 shows the distribution of the electrode load amount of the negative electrode according to Example 1, which shows a uniform distribution over the surface, and FIG. 15 shows the distribution of the electrode load amount of the negative electrode according to Comparative Example 1, and it was confirmed that there was variation in each region. [Explanation of symbols]

[0160] 10 electrodes 11 Electrode active material layer 11s surface area 11f bottom area 12 Electrode current collector 101 Center 102 Surface part

Claims

1. An electrode granule comprising an electrode active material and an electrode binder, the electrode active material is bound by the electrode binder, a content of the electrode binder in the surface portion is greater than a content of the electrode binder in the center portion, based on a total weight of the electrode active material and the electrode binder being 100 wt %; A granule for an electrode, wherein the surface portion is a region extending from the surface of the granule toward the center of the granule up to 30% of the radius, and the central portion is the portion other than the surface portion.

2. 2. The granule for an electrode according to claim 1, wherein the surface portion is a region from the surface of the granule toward the center of the granule up to 20% of the radius.

3. 2. The granule for an electrode according to claim 1, wherein the surface portion is a region from the surface of the granule toward the center of the granule up to 10% of the radius.

4. 2. The granule for an electrode according to claim 1, wherein the granule has an aspect ratio of 0.5 to 1.

0.

5. 2. The granule for an electrode according to claim 1, wherein the granule has an aspect ratio of 0.75 to 1.

0.

6. The particle size D of the granules 50 2. The granule for an electrode according to claim 1, wherein the particle size is 0.1 μm to 1,000 μm.

7. 10. The electrode granule according to claim 1, wherein the granule comprises two or more electrode active material materials.

8. A current collector; an electrode active material layer located on the current collector, An electrode for an electrochemical element, wherein the electrode active material layer comprises an electrode active material and an electrode binder, and the granules according to claim 1 are introduced and integrated into a layered structure.

9. 9. The electrode for an electrochemical element according to claim 8, wherein the electrode active material layer has a multi-layer structure in which two or more unit active material layers are laminated.

10. 9. The electrode for an electrochemical element according to claim 8, wherein a difference between a binder content (wt%) in an upper portion (100 wt%) and a binder content (wt%) in a lower portion (100 wt%) of the electrode active material layer is 10 wt% or less, the difference being between an upper portion and a lower portion when the electrode active material layer is divided based on a point 50% from a current collector in a thickness of the electrode active material layer.

11. 9. The electrode for an electrochemical element according to claim 8, wherein the difference in binder content between a region up to 15% of the thickness of the electrode active material layer from the current collector in a direction toward the electrode surface and a region up to 15% of the thickness of the electrode active material layer from the surface of the electrode active material layer in a direction toward the current collector is 10 wt % or less.

12. 9. The electrode for an electrochemical element according to claim 8, wherein the current collector has a primer layer disposed on at least one surface thereof, the primer layer covering the entirety or at least a portion of the surface, and comprising a second conductive material and a second binder.

13. An electrochemical element comprising a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, the negative electrode being the electrode according to claim 8.

Citation Information

Patent Citations

  • Method for preparing SiOx composite anode material

    CN105977463A

  • Method for producing negative electrode material for lithium ion secondary battery, negative electrode for lithium ion secondary battery, and lithium ion secondary battery

    JP2012134068A

  • Positive electrode active material composite material and use of the same

    JP2014035859A

  • Composite particles for electrochemical element electrode

    WO2006115272A1